Pelatihan Manajemen Digital di UMKM Bengkulu - Indah Oktari Wijayanti; Deasy Emalia; Nikmah Nikmah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Digital management training has become the main need for Micro, Small, and Medium Enterprises (MSMEs) in the era of digitalization. In Bengkulu, many MSMEs face challenges in adopting technology to improve operational efficiency, expand markets, and increase competitiveness. This study aims to analyze the impact of digital management training on increasing the management capacity of MSMEs in Bengkulu. This training includes an introduction to digital technology, online marketing strategies, application-based financial management, and customer data management. The results of the training show that the implementation of digital management has a significant positive impact on productivity, business management, and MSME revenue growth. The study also highlights the importance of ongoing support from the government and the private sector in facilitating the adoption of digital technology among MSMEs.